Endothelial vascular toxicity from chemotherapeutic agents: Preclinical evidence and clinical implications - Soultati, Aspasia; Mountzios, Giannis; Avgerinou, Chrysoula; Papaxoinis, George; Pectasides, Dimitrios; Dimopoulos, Meletios-Athanassios; Papadimitriou, Christos (Cancer treatment reviews, 2012)
In cancer biology angiogenesis plays a vital role in tumour growth and its subsequent metastatic potential. By targeting the angiogenic process, a new treatment strategy was added in the clinician’s therapeutic armamentarium. On the other hand, numerous classic cytotoxic agents are currently considered as potential angiogenesis inhibitors, although they were not originally developed as such, representing the so-called “accidental” anti-angiogenic drugs. The discovery of these new properties of classic cytotoxic agents led to the re-evaluation of their effect on vascular cells, rendering thus the endothelium an appealing target for therapeutic intervention, either with chemotherapy alone or with combination of cytotoxics with molecular angiogenesis inhibitors. Moreover, current evidence supports that chemotherapy-induced endothelial dysfunction constitutes an integrating predictive marker of future cardiovascular events and correlates well with traditional cardiovascular risk factors. It has therefore been suggested that evaluation of endothelial function may be useful in identifying asymptomatic subjects at high risk for cardiovascular events as well as for risk stratification of patients with established cardiovascular disease. Integration of the assessment of endothelial function in the clinical setting will thus enable effective intervention strategies to prevent or minimize the impact of these late adverse effects and design accurate follow-up protocols focused on cardiovascular complications. In the current review we provide a comprehensive overview of the effects of cytotoxic chemotherapeutic agents on endothelial function and the clinical implications of chemotherapy-associated endothelial toxicity in patients with cancer.